Verbal Sign on Coldplay’s Song “Biutyful” (Semiotic Analysis) - Ni Ketut Novia Anggreni; Ida Ayu Mela Tustiawati (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
The purpose of this study is to analyze and interpret the meanings or messages conveyed by the semiotic indicators present in three specific scenes from Coldplay's "Beautiful" music video. Data for this analysis was obtained from Coldplay’s official YouTube channel, ensuring authenticity and accuracy in the selection of the music video scenes. These verbal signs within the music video specifically numerals and taglines were evaluated using Roland Barthes' (1967) semiotic theory of denotative and connotative meanings. The data of this researchwere analysed by using descriptive qualitative method. This study focuses on the analysis of verbal signs, examining both their denotative and connotative meanings in the context of communication. The music video scenes contained three verbal signs. Ultimately, the findings of this research will shed light on the various layers of meaning embedded in the verbal signs of the music video. This includes understanding how these signs, wheninterpreted beyond their literal sense, contribute to the overall narrative and thematic depth of the video.